Prospective Approaches to the Sustainable Use of Peonies in Bulgaria - Christina Stoycheva; Daniela Batovska; Giuseppe Antonio Malfa; Rosaria Acquaviva; Giancarlo Statti; Ekaterina Kozuharova (Plants)
In Europe, Paeonia officinalis and P. peregrina, along with Chinese P. lactiflora, are commonly used for medicinal purposes. This comprehensive review summarizes the secondary metabolites and biological activities of P. peregrina, P. officinalis, P. tenuifolia, P. mascula, P. lactiflora, and the ornamental cultivars derived from the last taxon. Terpenoids, flavonoids, and phenolic acids are present in all five species, while tannins, lipids, and organic acids have been identified in only some. All five species exhibit antioxidant and antimicrobial potential, alongside anti-inflammatory, anticancer, neuroprotective, antisclerotic, antidiabetic, and various other bioactivities. The data were accessed via Scopus, Web of Science, PubMed, and Google Scholar search engines. The review also reveals that P. officinalis and P. lactiflora have been far more extensively studied than P. peregrina, P. tenuifolia, and P. mascula in terms of their chemical composition and pharmacological properties. The genus Paeonia L. comprises 37 accepted species, many of which are renowned for their ornamental and medicinal value. Native to Bulgaria are P. peregrina, P. tenuifolia, and P. mascula, with the latter two being protected by the Bulgarian Biodiversity Act. The collection of substances from all three species is subject to regulatory restrictions. This review reveals the possible use of P. lactiflora as a substitute for P. peregrina.